2019
DOI: 10.1523/jneurosci.3069-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Epoxyeicosatrienoic Acid Signaling in the Medial Prefrontal Cortex Modulates Depressive-like Behaviors

Abstract: Major depressive disorder is the most common mental illness. Mounting evidence indicates that astrocytes play a crucial role in the pathophysiology of depression; however, the underlying molecular mechanisms remain elusive. Compared with other neuronal cell types, astrocytes are enriched for arachidonic acid metabolism. Herein, we observed brain-region-specific alterations of epoxyeicosatrienoic acid (EET) signaling, which is an arachidonic acid metabolic pathway, in both a mouse model of depression and postmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 37 publications
(49 reference statements)
2
30
1
Order By: Relevance
“…EETs have vasodilatory and anti-inflammatory actions, and pathophysiologic features of AD include early vascular damage and progressive inflammation (De Strooper and Karran, 2016;Wu et al, 2017). We recently reported that, in the brain, sEH is mainly localized in the lysosomes of astrocytes and plays an important role in regulating astrocyte function (Qin et al, 2019;Xiong et al, 2019). In the present study, we tested the hypothesis that sEH contributes to the pathophysiology of AD through the modulation of Ab metabolism in astrocytes.…”
Section: Introductionmentioning
confidence: 88%
“…EETs have vasodilatory and anti-inflammatory actions, and pathophysiologic features of AD include early vascular damage and progressive inflammation (De Strooper and Karran, 2016;Wu et al, 2017). We recently reported that, in the brain, sEH is mainly localized in the lysosomes of astrocytes and plays an important role in regulating astrocyte function (Qin et al, 2019;Xiong et al, 2019). In the present study, we tested the hypothesis that sEH contributes to the pathophysiology of AD through the modulation of Ab metabolism in astrocytes.…”
Section: Introductionmentioning
confidence: 88%
“…A recent study has demonstrated that lipid signaling in PFC astrocytes modulates depressive-like behaviors [ 38 ]. Producing an increase in epoxyeicosatrienoic acid (EET) by injecting a mixture of inhibitors hydrolyzing EET into the PFC reduces CSDS-elicited immobility in FST, whereas the infusion of a selective antagonist of EET increases immobility in the same test.…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…All the experiments were conducted following the Chinese Council on Animal Care guidelines. All the behavioral tests were conducted following the procedures established in our laboratory, with some modifications ( Cao et al, 2013 ; Qin et al, 2019 ; Wang et al, 2019 ; Xiong et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The methodology for the CMS paradigm was as previously described ( Cao et al, 2013 ; Qin et al, 2019 ; Xiong et al, 2019 ). Mice were briefly individually caged and habituated to water or a 1% sucrose solution for the assessment of the baseline sucrose preference.…”
Section: Methodsmentioning
confidence: 99%